2006
DOI: 10.1111/j.1365-3148.2006.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing indications for red cell transfusion from 2000 to 2004 in the North of England

Abstract: Falling donor numbers and the threat of transfusion-transmitted variant Creutzfeldt-Jakob disease may lead to shortages in the national blood supply. Knowledge of current patterns of transfusion and trends in usage will help predict future change in blood use. Our previous survey identified medical indications as the major reason for transfusion, but detailed information within this category was limited. We performed prospective surveys of indications for red cell transfusion for two 14-day periods in 2004 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
83
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 12 publications
10
83
2
Order By: Relevance
“…The requirement of blood arises more in these cases due to anemia secondary to anorexia, cancer cachexia, bone marrow suppression in cases of leukemias or chemotherapy, etc. Similar high percentage of blood utilization for patients with malignances have been reported in several studies [6,7,11,12].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The requirement of blood arises more in these cases due to anemia secondary to anorexia, cancer cachexia, bone marrow suppression in cases of leukemias or chemotherapy, etc. Similar high percentage of blood utilization for patients with malignances have been reported in several studies [6,7,11,12].…”
Section: Discussionsupporting
confidence: 65%
“…Similarly scenatrio has been reported by many workers [12][13][14][15][16]. However, studies like that of Wallis et al have reported more supply to medical patients (62%) as compared to 33% to surgical patients [11].…”
Section: Discussionmentioning
confidence: 66%
“…is result is similar to our study and a study of United Kingdom. 10,11 But, another study from England di ered from these studies showing more surgical cases than medical cases among patients receiving blood transfusions. 12 Results were found di erent in di erent region.…”
Section: Discussionmentioning
confidence: 99%
“…12 Results were found di erent in di erent region. For example, in case of red cells used in hematology, North England showed 15.5% in 2002 9 , 18.2% in 2006 (excluding iron de ciency anemia) 11 , South-east England showed 13.1% in 2002 12 . Victoria of Australia showed 23.8% in 2009 (including hematinic de ciency, benign and malignant hematology) 13 , South Australia showed 27% (including all hematologic conditions) 10 , and our study (in Faridpur, Bangladesh) showed 37% (including all hematological conditions).…”
Section: Discussionmentioning
confidence: 99%
“…A study from the United Kingdom found that this indication alone accounts for 14% of the national red cell supply [11]. There is a widespread variation in clinical practice that influences transfusion threshold, due to several factors including physician, patient factors, and hospital local guidelines.…”
Section: Resuscitation and Initial Assessmentmentioning
confidence: 99%